2021
DOI: 10.18826/useeabd.998178
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Avrupa Liglerinde Oynanan Futbol Müsabakalarında Atılan Gollerin Teknik ve Taktik Analizi: Bundesliga, La Liga, Premier Lig

Abstract: gol öncesinde yapılan pas sayısı, gol öncesi geçen süre, atılan gollerin bölgesi (ceza sahası içi ve dışı), golün hangi bölgeden geliştiği, golün geliştiği bölgede vücudun hangi uzvuyla yapıldığı, penaltıların olumlu-olumsuz durumu, sarı-kırmızı kart, kornerler, merkez-kanat duran toplar, frikik sayıları gibi parametrelerden oluşmaktadır. Araştırmada elde edilen bütün veriler, SPSS (version 18.0) programında kayıt altına alınmış olup, öncelikle fekans ve yüzde değerleri hesaplanmıştır. Farklı ülke liglerinin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, teams' in-game strategies and tactics should also be considered as an important factor. Yavuz and Saygın (2021) reported in their analysis of matches played in the 2020-2021 season in the English Premier League (196 matches), German Bundesliga (65 matches), and Spanish La Liga (50 matches) that in the Premier League, 25.4% (113 goals) of the total goals were scored from the left wing, 46.7% (207 goals) from the center, and 27.9% from right wing attacks, while in the German Bundesliga, these rates were 29.4% (56 goals), 34% (65 goals), and 36.6% (70 goals), and in the Spanish La Liga, these rates were 31.6% (35 goals), 47.7% (53 goals), and 20.7% (23 goals) respectively (Yavuz & Saygın, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, teams' in-game strategies and tactics should also be considered as an important factor. Yavuz and Saygın (2021) reported in their analysis of matches played in the 2020-2021 season in the English Premier League (196 matches), German Bundesliga (65 matches), and Spanish La Liga (50 matches) that in the Premier League, 25.4% (113 goals) of the total goals were scored from the left wing, 46.7% (207 goals) from the center, and 27.9% from right wing attacks, while in the German Bundesliga, these rates were 29.4% (56 goals), 34% (65 goals), and 36.6% (70 goals), and in the Spanish La Liga, these rates were 31.6% (35 goals), 47.7% (53 goals), and 20.7% (23 goals) respectively (Yavuz & Saygın, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ağyol and Tanyeri (2022) found out that the goals scored during 2020 Europe Football Championship were more in the second half of the games and they were scored by midfield players with backward passing and as a result of organized offence starting from the midfield (1). Yavuz and Saygın (2021) concluded that teams of the British Premiere League were more successful than other teams in the league in Europe in respect to offence preparation and goal formation parameters (20). Hadi and Göral (2020) suggested that minutes between 46 th -60 th are when goals are scored most in 2020 Europe Football…”
Section: Discussionmentioning
confidence: 99%